Control of Syar’i Ghibah Practices Using Six Sigma and SWOT Analysis to Enhance Islamic Ethical Culture in Educational Settings - Novita Anggraeni; Fahmiyah Tsaqofah Islamiy; Nur Fatimatus Zahro; Nofiatul Syafitri; Eni Fariatul Fahyuni (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Ghibah (backbiting) remains a common communication problem in educational environments, including those with strong religious values. This study aims to develop a Sharia-based model for controlling ghibah by integrating the Six Sigma (DMAIC) method and SWOT analysis to improve Islamic communication ethics. A mixed-methods approach was used, involving 235 educators from three types of institutions. Data were collected through questionnaires, interviews, and observations, then analyzed using Six Sigma indicators along with thematic and SWOT analysis. The results show that ghibah behavior is still prevalent, especially in the form of involvement as both listeners and speakers. The initial sigma level (2.3–2.6) indicates weak behavioral control. After implementing interventions such as Islamic communication training, SOP development, and awareness programs, the sigma level improved to above 3.0 in several indicators. In conclusion, the integration of Six Sigma and SWOT within an Islamic ethical framework is effective in reducing ghibah behavior, although sustainable change requires continuous institutional support.